Analisis Prokrastinasi Akademik Siswa di Sekolah - Erfan Ramadhani; Hikmatus Sadiyah; Ramtia Darma Putri; Rizky Andana Pohan (Consilium : Berkala Kajian Konseling dan Ilmu Keagamaan, 2020)
Procrastination is a behavior that is not good or negative behavior including; neglect in completing assignments, and lack of punctuality when entering school hours. Based on the results of research in the field, it appears that there are students who take academic procrastination, procrastination conducted in the form of procrastinating in completing assignments that result in students being hampered in the learning process at school. This research uses quantitative descriptive methods. The subjects of this study were students of the State High School 1 Muara Sugihan Banyuasin Regency class XII. Based on the results of this study it can be seen that the academic procrastination of Muara Sugihan Middle School 1 Middle School students in Banyuasin Regency is in the High category with a score of 90.92. Thus the expectation of handling the problem is expected so that students can solve the problem. One way to treat the problem is counseling services